THE PERSONALITY OF THE ACCUSED AS AN OBJECT OF STUDY OF THE INQUIRY BODY IN CRIMINAL PROCEEDINGS OF THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the personality of not only the accused, but also the suspect as an object of study by the investigative body for criminal proceedings of the Kyrgyz Republic. The author concludes that the concept of “personality” in criminal procedure law is used primarily for study by investigative bodies that are ordered to perform actions within their competence. The study of personality, recognition of characteristic significant features of the accused, rational use of the collected information in the process of solving and investigating crimes is extremely important for collecting evidence in pre-trial proceedings and when sentencing for the court
Keywords: body of inquiry, national security, pre-trial proceedings, investigation, crime, prevention, investigator.